The Impact of Accounting Information Systems on Internal Control of Fixed Assets at the Education Office of West Java - Ashari Mansur Mahmudin; Maulana Yusup (P3M, STIE Pasundan, Bandung, Indonesia., 2026)
Effective management of public sectors requires rigorous oversight, yet organizations frequently encounter vulnerabilities in safeguarding state-owned wealth. Specifically, the Education Office of West Java faces critical challenges in maintaining the accountability and security of its fixed assets, often due to fragmented tracking and inadequate oversight mechanisms. This study investigates the impact of Accounting Information Systems (AIS) on the internal control of fixed assets at the Education Office of West Java. By analyzing this relationship, the research aims to determine how digitalized accounting frameworks can optimize asset safeguarding and reporting accuracy. The research employs a quantitative survey approach to gather primary data. The target population comprises administrative and financial staff within the institution, from which the study draws a sample of 40 operational employees directly involved in asset management. The data analysis utilizes structural equation modeling or multiple linear regression analysis (processed via statistical software) to evaluate the reliability, validity, and statistical significance of the system's impact on internal control measures. The statistical results demonstrate that the Accounting Information System exerts a significant positive impact on the internal control of fixed assets at the Education Office of West Java. Higher levels of AIS implementation directly correlate with stronger, more transparent, and highly efficient asset control mechanisms. While previous literature extensively covers AIS in private corporate sectors, this study offers fresh insights by contextualizing these dynamics within a regional public education department. It bridges the empirical gap regarding how localized bureaucratic structures adapt to automated accounting controls. The findings imply that government institutions must prioritize the modernization of their accounting software and provide continuous technical training for staff. Implementing these systemic upgrades will minimize the risk of asset misappropriation, ensure compliance with regional audit standards, and ultimately enhance public trust in institutional financial management.